Mapas da territorialização viticola portuguesa (1865-1908) - Fernandes, Mário Gonçalves (2021)
In the European Union, particularly following the reform of the common agricultu-ral policy in 1992, efforts were made to combine policies of intensification, partial-ly based on the material and immaterial memories of rural territories which have always been characterised by a dense and diverse historical depth. The protected designations of origin and protected geographical indications are tied to circums-cribed areas which represent autarkies and concretes ways of doing, thus merging tradition with specificity and identity. However, these efforts were not really a novelty, since in the specific case of Euro-pean viticulture, the quality of the wines has for centuries been associated to the virtuous combination of soil, climate, sunlight and grape varieties. These factors have long been territorialised, as in the case of the demarcation of the Douro region in Portugal in 1756, during the government of the Marquis of Pombal. During the 1800s, particularly after the crisis arising from the mid-century powde-ry mildew plague, which led to an organoleptic restructuring in which some less resistant varieties disappeared, and the advent of phylloxera in the 1860s, successive measures were taken to protect the individuality of wines. This implied defi-ning their territoriality. In this paper, in a second approach to a number of 19th-century cartographic sour-ces related with viticulture, we intend to explore the forms and modalities adopted in defining this territoriality and to analyse the cartographic documents selected, among which those by Emiliano Augusto de Bettencourt, from 1874; those coordi-nated by E mile C. D'Oliveira Pimentel, from 1878; the maps of Jose Taveira de Car-valho Pinto de Meneses, from 1888 and 1889. Finally, we will examine how Portu-gal proceeded with the demarcation of its winegrowing regions very early on, in 1907 and especially in 1908, the latter being mostly adjusted to the regions' pa-rishes, corresponding essentially to the main Portuguese wine regions still existing today.